Post - Reformasi Writing in Indonesia: The Rise of Plural Voices Beyond State Narratives - Dari, Serli Wulan (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
The transformation of Indonesian historiography from the centralized and hegemonic pattern of the New Order to a more plural form in the post-Reformasi era, and its implications for writing the history of Islamic civilization. During the New Order, the state monopolized the production of historical knowledge through curricula, textbooks, films, the Indonesian National History project, and strict control over archives and sensitive themes such as the 1965–66 massacres, state violence, and ethnic conflicts. The 1998 Reformasi disrupted this singular authority and opened space for non-state actors independent scholars, local communities, pesantren, victims’ organizations, women’s activists, and investigative journalists to articulate alternative narratives highlighting the experiences of marginalized groups. This pluralization encouraged the development of local history, women’s history, oral history, and multidimensional as well as phenomenological approaches that integrate written archives, oral testimonies, and cultural sources. In the study of the history of Islam in Indonesia, the focus is no longer limited to the state and canonical ulama, but also includes local ulama networks, Sufi orders, pesantren, and the everyday lives of Muslim communities. The article argues that post-Reformasi openness not only enriches historical themes and actors but also demands methodological and ethical renewal, so that pluralization does not collapse into relativism but instead leads toward a more democratic, reflective, and inclusive historiography.